Evolutionary history of the little fire ant Wasmannia auropunctata before global invasion: inferring dispersal patterns, niche requirements and past and present distribution within its native range - Chifflet, Lucila (2016)
The evolutionary history of invasive species within their native range mayinvolve key processes that allow them to colonize new habitats. Therefore,phylogeographic studies of invasive species within their native ranges areuseful to understand invasion biology in an evolutionary context. Here weintegrated classical and Bayesian phylogeographic methods using mitochondrialand nuclear DNA markers with a palaeodistribution modelling approach, to infer the phylogeographic history of the invasive ant Wasmannia auropunctata across its native distribution in South America. We discuss our results in the context of the recent establishment of this mostly tropical species in the Mediterranean region. Our Bayesian phylogeographic analysis suggests that the common ancestor of the two main clades of W. auropunctata occurred in central Brazil during the Pliocene. Clade A would have differentiated northward and clade B southward, followed by a secondary contact beginning about 380 000 years ago in central South America. There were differences in the most suitable habitats among clades when considering three distinct climatic periods, suggesting that genetic differentiation was accompanied by changes in niche requirements, clade A being a tropical lineage and clade B a subtropical and temperate lineage. Only clade B reached more southern latitudes, with a colder climate than that of northern South America. This is concordant with the adaptation of this originally tropical ant species to temperate climates prior to its successful establishment in the Mediterranean region. This study highlights the usefulness of exploring the evolutionary history of invasive species within their native ranges to better understand biological invasions.